Calaqsız yolun bərkidicilərinin avtomatlaşdırılmış diaqnostikasının aparılmasının tədqiqi - Cəfərov, Bəhram; Kərimov, Zəka; Hüseynov, Ağalar (My University, 2024)
The safe operation and technical-economic efficiency of an unpaved road depend not only on the requirements for its construction, paving, repair, and maintenance but also on the preparation of road works, including the level of readiness of the engineering equipment.
Research of the automated diagnostics of stabilizers of the unpaved road
Keywords: Calaqsız yolun dayanıqlığı; Calaqsız yolun bərkidiciləri; Stability of the unpaved road; Stabilizers of the unpaved road